Wear rate analysis of main blades of a rotary cutting machine - Marcelo, Eisson M.
This study investigates the trend of wear on the main blades of a rotary cutting machine, analyzes the maximum allowable materials it can shred for usable blade service, and determines the significant factors that affect its rate of wear. The experimental design is unreplicated with 16 responses from 4 blade positions, 2 feed materials, and 2 rotational speeds. The experimental method used for the system being analyzed are the mass difference method, linear wear dimension method, and wear area method; all through offline monitoring of wear. The experimental tests were composed of 4 factor combinations. Each experimental test has a feed material of 2 tons with 10 overall trials to record the progression of the blade wear. A digital analytic balance was employed for the mass difference method; and a digital single lens reflex (DSLR) camera to obtain photographs was employed, both for the linear wear dimension and wear area methods. Four wear criteria were established for analyzing the data: total wear area, cutting edge wear area, average cutting edge angle, and mass difference. The machine behavior and output were analyzed based on the combination of factors for experimental tests. The trend of wear across the blade length shows that the highest effect of wear are on the outermost part of the blade. The usable blade service was based on valid blade predictors using linear regression. The Coconut Feed has a higher usable blade service at High Speed, while the opposite is the case for the Glass Feed with a higher usable blade service at Low Speed. The Analysis of Variance (ANOVA) was used for the factorial design of experiment. For the main effects, the most to least significant factors are: (1) the change of feed material, (2) the change of rotational speed, (3) the variation of blade position. For the interaction effects, the most to least significant combinations are: (1) feed material & rotational speed, (2) blade position & feed material, (3) blade position & rotational speed.